2014
DOI: 10.4314/ahs.v14i3.24
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <i>Chlamydia trachomatis</i> infection among patients attending infertility and sexually transmitted diseases clinic (STD) in Kano, North Western Nigeria.

Abstract: Background: Chlamydia trachomatis is the most common bacterial sexually transmitted disease in the world with severe complications. The aim of this study was to determine the prevalence and possible risk factors of C. trachomatis in Kano. There is dearth of information on this subject in this locality. Method: Urine samples, Endocervical swabs and Urethral swab were collected from consecutive patients attending the Infertility and STD clinics in Aminu Kano Teaching Hospital (AKTH) between June and December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
14
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 8 publications
12
14
4
Order By: Relevance
“…The prevalence of chlamydial infection in infertile women in this study was 8%. Similar prevalence was found in studies carried out in Oman (5.5%) [43], Central Saudi Arabia (8%) [26], Poland (8.7%) [44], Nigeria (9.6%) [35] and Brazil (10% and 10.9%) [39] [45]. However, higher prevalence was found by others studies carried out in Saudi Arabia (15%) [28], UK (16%) [36], India (28.1%) [46] and Iran (32%) [34].…”
Section: Discussionsupporting
confidence: 65%
“…The prevalence of chlamydial infection in infertile women in this study was 8%. Similar prevalence was found in studies carried out in Oman (5.5%) [43], Central Saudi Arabia (8%) [26], Poland (8.7%) [44], Nigeria (9.6%) [35] and Brazil (10% and 10.9%) [39] [45]. However, higher prevalence was found by others studies carried out in Saudi Arabia (15%) [28], UK (16%) [36], India (28.1%) [46] and Iran (32%) [34].…”
Section: Discussionsupporting
confidence: 65%
“…all low-risk factors for STIs, this finding is comparable with the study done in Nigeria (18.2%) [11], Taiwan (18.4%) [12], Gaza, Palestine (20.2%) [13]and the Solomon Islands (20.3%) [14]. Itis possible that the prevalence of CT infection reported in our study represents a true picture of the disease since the reported condom usage was very low, which may suggest further investigation of other risk behaviors like non-monogamous spouses [15]. In contrast to our finding, higher rates of CT infection were reported in women attending gynecology clinics in Mbarara, Uganda (26.5%) [16], Jos, Nigeria (51.6%) [17]and South Eastern Nigeria(40.7%) [18].…”
Section: Discussionmentioning
confidence: 90%
“…Its prevalence is about 5% (CDCP, 2009). In South Africa, the reported infection rates were higher (5.9-33%) among general populations showing a big regional difference (Buve et al, 2001;Isibor et al, 2005;Nwankwo and Sadiq, 2014). Therefore CT has been the main target for general population screening.…”
Section: Introductionmentioning
confidence: 99%